ANALISIS BIAYA PRODUKSI DAN TITIK IMPAS USAHA KECIL PEMBUATAN SARI JAHE INSTAN - Makmur (Fakultas Ekonomi Universitas Pasir Pengaraian, 2016)
This research aims to detect cost of goods manufactured and break even point sarijahe instan Rokan Hulu Regency. performed on december 2014 until with may 2015. Thisresearch intent to know cost structure, cost of goods manufacture, income, and break evenpoint efficiency of sari jahe instan. This research constitute case study on Sari Jahe InstanZahra belongs to Sumartini's in Rambah Utama village, district Rambah Samo, Rokan HuluRegency. with respondent as source of observational data information is effort owner that ata swoop manager and employ as much 3 person. Result observationaling to point out thatCost structure consisting of Fixed Cost as big as Rp 108.300,- and variable cost as big asRp 2.082.000,- Full scale production cost as big as Rp 2.190. 300,- Effort acceptance as bigas Rp 2.880.000,- its outgrows propertied be Rp 689.700,- with point r/c ratio as big as 1,31meanwhile total BEP productions as much 274 boxs and BEP assesses Rp 6.084,-/box.